2021
DOI: 10.14309/ctg.0000000000000385
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Recognition of Atrophic Gastritis and Intestinal Metaplasia on White Light Endoscopic Images Based on Convolutional Neural Networks: A Multicenter Study

Abstract: INTRODUCTION: Patients with atrophic gastritis (AG) or gastric intestinal metaplasia (GIM) have elevated risk of gastric adenocarcinoma. Endoscopic screening and surveillance have been implemented in high incidence countries. The study aimed to evaluate the accuracy of a deep convolutional neural network (CNN) for simultaneous recognition of AG and GIM. METHODS: Archived endoscopic white light images with corresponding gastric biopsies were collected from 14 hospitals locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
(24 reference statements)
0
19
0
Order By: Relevance
“…Two studies ( 43 , 47 ) were from the same team, one of which ( 47 ) constructed and tested a CAG diagnostic model, and the other ( 43 ) performed a further test; hence, we selected the more extensive test set of data ( 43 ) included in this meta-analysis. Two other studies ( 41 , 48 ) were also from the same team; one study ( 41 ) used AI to identify AG and IM, and another study ( 48 ) added the identification of GC to the former, and we chose the first ( 41 ) to be included in this meta-analysis. Three studies were excluded because only IM was identified ( 49 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies ( 43 , 47 ) were from the same team, one of which ( 47 ) constructed and tested a CAG diagnostic model, and the other ( 43 ) performed a further test; hence, we selected the more extensive test set of data ( 43 ) included in this meta-analysis. Two other studies ( 41 , 48 ) were also from the same team; one study ( 41 ) used AI to identify AG and IM, and another study ( 48 ) added the identification of GC to the former, and we chose the first ( 41 ) to be included in this meta-analysis. Three studies were excluded because only IM was identified ( 49 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the computer-aided detection system proposed in one study achieved diagnostic accuracy for gastric precancerous conditions comparable to that of experts and superior to that of nonexperts [ 19 ]. Furthermore, deep convolutional neural network recognition of atrophic gastritis and gastric IM was achieved in another study [ 20 ]. However, the European Society of Gastrointestinal Endoscopy guidelines recently addressed the potential usefulness of AI systems, stating that AI-assisted diagnosis of atrophy and IM should be comparable to that provided by the established biopsy protocol, including extent estimation and subsequent allocation to the appropriate endoscopic surveillance interval [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that deep learning models can achieve 87% to 99.18% accuracy in the recognition of IM. 38,40,41 As noted above, most of this research has been focused on image recognition; the clinical value of existing models remains unclear. A few test videos have shown that the models require demanding environmental conditions to achieve the desired recognition effect.…”
Section: Applications Of Ai In Upper Gastrointestinal Tract Lesion De...mentioning
confidence: 99%
“…36 In their efforts to establish an AI model for atrophic gastritis detection, Guimaraes et al 37 achieved 93.0% accuracy by training the model with 200 images. Lin et al 38 replicated this approach with greater accuracy, achieving 96.4% accuracy in the detection of atrophic gastritis; they also detected intestinal metaplasia with 97.6% accuracy. Furthermore, researchers in China demonstrated that a trained AI model could review dynamic video and detect CAG with 92.37% accuracy 39 ; the key aspect of their work was its demonstration that an AI model could identify CAGs by assessing clinical videos.…”
Section: Applications Of Ai In the Detection Of Pre-cancerous Gastric...mentioning
confidence: 99%